Electromechanical and thermophysical processes in the pulse induction accelerator of plasma formation - K. V. Korytchenko; V. F. Bolyukh; S. G. Buriakovskyi; Y. V. Kashansky; O. I. Kocherga (Electrical engineering & Electromechanics, 2023)
Introduction. Work on the creation and throwing of plasma formations is carried out in the world's leading scientific centers in various ways. The creation of a plasma formation with duration of several milliseconds and its acceleration in an open atmospheric environment to a distance of 0.5-0.6 m was achieved. To create plasma, the energy of the primary discharge circuit is used, followed by the acceleration of the gas-plasma formation with the help of the energy of the secondary circuit. Plasma formation is also obtained due to the electric explosion of a conductor in a rapidly decreasing strong magnetic field, etc. The purpose of the article is a theoretical and experimental study of electromechanical and thermophysical processes in a pulsed induction accelerator, which ensures the creation of plasma formation due to thermal ionization as a result of the electric explosion of the conductor and its throwing in the atmospheric environment relative to the inductor. Method. For the analysis of electromechanical and thermophysical processes in the pulse induction accelerator of plasma formation (IIPP), a mathematical model of the accelerator was developed and implemented in the Сomsol Multiphysics software package, in which the anchor does not change its shape and aggregate state during operation and takes into account the parameters of the accelerator distributed in space. Results. Calculated electromechanical and thermal characteristics of the accelerator. It is shown that the temperature rise in the aluminum foil anchor is significantly uneven. The maximum temperature value occurs in the middle part of the foil closer to the outer edge, and this temperature is significantly higher than the boiling point of aluminum. Scientific novelty. Experimental studies of the IIPP were carried out, in which the armature is made of aluminum and copper foil, and the inductor connected to the high-voltage capacitive energy storage device is made in the form of a flat disk spiral. It was established that during the operation of the IIPP, the armature goes into a plasma state and moves vertically upwards, turning into a three-dimensional lump or a pile of small particles that rose to a considerable height relative to the inductor. Experimentally, the characteristic circular circuit of thermal heating of the copper foil of the anchor, which is fixed on a glass-textolite sheet, is shown, which indicates a similar nature of plasma formation. Practical value. The results of experimental studies with an accuracy of up to 15 % coincide with the calculated ones and show the validity of the IIPP concept, in which, due to the high density of the induced current in the armature, thermal ionization occurs as a result of an electric explosion of the conductor with its transition to the plasma state. And the interaction of the plasma formation with the magnetic field of the inductor leads to the appearance of an electrodynamic force that ensures its movement in the open atmospheric environment.